PROJECT-BASED DRAMA LEARNING IN REDUCING STUDENTS’ SPEAKING ANXIETY - A. K. Amarullah; Noor Rachmawaty (Fakultas Ilmu Budaya, Universitas Mulawarman, 2019)
Project-based Drama Learning (PBDL) is a learning model designed for both language learning and language teaching. In this case, PBDL gives a positive contribution to students’ language engagement and development. It provides a natural context for learning English. They learn not only the language that existed in the drama or the novel they read, but also the spontaneous language they use when they are doing their project. Referring to the significant contribution of PBDL and the urgency in helping pre- service English teachers at the English Department, Mulawarman University to perform well in their speaking, therefore the researcher intends to replicate the implementation of PBDL conducted by the previous researchers in the researchers’ English Drama course. The participants of this study were 27 students who enrolled in the researchers’ English Drama Course. This study was experimental. Speaking anxiety questionnaire was used by the researcher to find out students’ speaking anxiety level before and after the PBDL was implemented. Paired samples t-test was conducted to compare the level of speaking anxiety of students before and after PBDL was implemented. There was no significant difference found in students’ speaking anxiety levels before and after the treatment. Further investigation using different design and instruments needs to be carried out in order to reveal the insignificant effect of PBDL in reducing students’ speaking anxiety.